Decentring leisure : rethinking leisure theory - Rojek, Chris (Theory, culture & society (Unnumbered), 1995)
This book explores the meaning of leisure in the context of key social formations of our time. Chris Rojek brings together the insights of feminsim, Marxism, Weber, Elias, Simmel, Nietzsche and Baudrillard to produce a survey - and rethinking - of leisure theory. At the same time he presents a radical critique of the traditional c̀entring' of leisure, on èscape', f̀reedom' and c̀hoice'. He describes the relations between capitalism and leisure, the meaning of free time for workers in a capitalist system, and the gendered nature of leisure. He then discusses the social construction of leisure.